Ideal concentration of turmeric to be added to artisanal cassava flour according to consumer preference - ÁLVARES, Virgínia de Souza; REIS, Ronielli Cardoso; SOUZA, Joana Maria Leite de; LAMBERTUCCI, Daniel Moreira; SANTIAGO, Antônio Clebson Cameli (Food Science and Technology, 2024)
In the artisanal manufacture of yellow cassava flour, in the North region of Brazil, it is common to add turmeric. However, there are no recommendations on this process considering the preference of consumers. The present study proposes to determine this ideal concentration of turmeric that should be added to cassava flour based on consumers’ preference. Samples were produced with 0, 0.05, 0.10, 0.15, and 0.20% concentrations of turmeric in the flour. The flours were evaluated for moisture, ash, ether extract, fiber, protein, acidity, pH, aw, and instrumental color. Sensory evaluation was analyzed in the cities of Rio Branco and Cruzeiro do Sul, state of Acre, Brazil. The addition of turmeric promoted an increase in acidity and a reduction in moisture and water activity of the flours. The intensity of the yellow color increased as higher concentrations of turmeric were added. Sensory tests using the hedonic, ideal, and purchase intention scales and internal preference mapping revealed differences between the two municipalities in terms of preference of consumers. In Rio Branco, there was a preference for flours with intermediate concentrations of turmeric, from 0.05 to 0.15%, while Cruzeiro do Sul recommended a concentration of 0.05% of turmeric.